2014
DOI: 10.1021/ie501784c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Epoxidation Activity of Tungsten-Incorporated SBA-16 (W-SBA-16)

Abstract: Tungsten, in varying amounts, was incorporated into a SBA-16 structure via a one-pot direct synthesis method under an acidic medium using Pluronic F127 triblock co-polymer as a template and n-butanol as a co-surfactant. Tetraethyl orthosilicate (TEOS) and sodium tungstate were used as the Si and W sources, respectively. The resulting materials (denoted as W-SBA-16) are characterized for structural ordering, textural properties, and types of tungsten incorporation by techniques such as small-angle X-ray scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 29 publications
5
53
0
Order By: Relevance
“…On the other hand, the excessive addition of tungsten source easily promotes the form transformation from incorporated tungsten species to isolated tungsten species or low oligomeric tungsten oxide species, and finally to crystalline WO 3 . It has been reported that incorporated tungsten species, isolated tungsten species, and low oligomeric tungsten oxide species, rather than crystalline WO 3 were powerful active sites for a variety of reactions [31,32,46,49]. In our study, three above tungsten species forms were indeed beneficial to the enhancement of photocatalytic efficiency, possibly owing to the quite intimate connection between framework of SBA15 and tungsten species, thus facilitating to transfer photogenerated electrons to SBA15 matrix and further transfer them by means of electron delocalization capacity from SBA15 framework [30], effectively avoiding the recombination of charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the excessive addition of tungsten source easily promotes the form transformation from incorporated tungsten species to isolated tungsten species or low oligomeric tungsten oxide species, and finally to crystalline WO 3 . It has been reported that incorporated tungsten species, isolated tungsten species, and low oligomeric tungsten oxide species, rather than crystalline WO 3 were powerful active sites for a variety of reactions [31,32,46,49]. In our study, three above tungsten species forms were indeed beneficial to the enhancement of photocatalytic efficiency, possibly owing to the quite intimate connection between framework of SBA15 and tungsten species, thus facilitating to transfer photogenerated electrons to SBA15 matrix and further transfer them by means of electron delocalization capacity from SBA15 framework [30], effectively avoiding the recombination of charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reported cubic mesoporous silica materials, SBA-16 appears to be one of the best candidates as catalytic support or absorbent because of the enhanced thermal stability due to the thick wall, economical synthesis with inexpensive silica sources, and large pores [67][68][69][70]. Sn incorporated SBA-16 (Sn-SBA-16), as an ordered cubic-like mesoporous structure, gives Lewis acid sites through the framework substitution for silica matrix.…”
Section: Sn-containing Mesoporous Materials Catalystsmentioning
confidence: 99%
“…However, incorporation of tungsten into mesoporous silicates is not a trivial task since tungsten is considerably larger than silicon, with an ionic radius of 0.42 Å, compared to 0.26 Å [19]. Thus, tungsten-containing mesoporous molecular sieves usually have a serious drawback of the active metal leaching under turnover conditions of liquid-phase oxidation [20][21][22][23][24]. Numerous efforts have been focused on synthesizing materials in which the active tungsten species are well isolated and anchored on the support through W-O-Si covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been focused on synthesizing materials in which the active tungsten species are well isolated and anchored on the support through W-O-Si covalent bonds. In recent years, tungsten has been incorporated into high surface area mesoporous molecular sieves, such as MCM-41 [21,[25][26][27][28][29][30][31], MCM-48 [32,33], SBA-15 [34][35][36], SBA-16 [23], HMS [37,38], MCF [39,40], KIT-5 [41], KIT-6 [24,42], and TUD-1 [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation